Effect of the mannose-binding Artocarpus integer lectin on the cellular proliferation of murine lymphocytes - Lim, S.B.; Kanthimathi, M.S.; Hashim, Onn Haji (Taylor & Francis, 1998)
The effect of the mannose-binding champedak (Artocarpus integer) lectin-M on the cellular proliferation of murine lymphocytes was investigated in this study. Our data demonstrated that the lectin was the main mitogenic component in the crude extract of the champedak seeds. It stimulated the proliferation of murine T cells at an optimal concentration of 2.5 mu g/ml in a 3 day culture. Lectin-M appeared to be a T-cell mitogen as it does not induce significant DNA synthesis when cultured with spleen cells from the nude mouse. In the absence of T cells, the lectin was incapable of inducing resting B cells to differentiate into immunoglobulin secreting plasma cells.